THE FIRST BOSNIAN-TURKISH/TURKISH BOSNIAN LEXICOGRAPHIC WORK - Edina Ustavdić (Human Research in Rehabilitation, 2011)
In this work, the authoress interprets the frst Bosnian-Turkish/Turkish-Bosnian dictionary Maqbul-i ‘Arif, or better known as Potur Shahidi written by Muhammed Hevai Uskuf, a Bosnian Muslim, born in Tuzla, Bosnia and Herzegovina, in 1631 (Hevaji, 1724).